2020
DOI: 10.24252/as.v12i1.10283
|View full text |Cite
|
Sign up to set email alerts
|

Teaching under stress and fatigue: Can affect of the performance?

Abstract: Workload, work stress, work fatigue, and performance are important variables in an organization, which must be well organized so that the organization can run well and succeed. The purpose of this study was to determine the relationship between workload, work stress, work fatigue, and teacher performance. The research design used was cross-sectional in 38 teachers of SMP Negeri 3 Bandung city taken in total sampling. The instrument was adopted from previous studies which have been validity and reliability test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While studies showed a constant relationship between academic stress and cyberloafing, a further evaluation towards the role of fatigue was also observed. This is supported by Yogisutanti et al (2020), who observed that individuals experiencing heightened work-related stress were more prone to becoming fatigued and may seek extraneous activities for relief. The premise of relief through this study, could be further disguised as that of cyberloafing.…”
Section: Literature Reviewmentioning
confidence: 70%
See 1 more Smart Citation
“…While studies showed a constant relationship between academic stress and cyberloafing, a further evaluation towards the role of fatigue was also observed. This is supported by Yogisutanti et al (2020), who observed that individuals experiencing heightened work-related stress were more prone to becoming fatigued and may seek extraneous activities for relief. The premise of relief through this study, could be further disguised as that of cyberloafing.…”
Section: Literature Reviewmentioning
confidence: 70%
“…The results of the second hypothesis show that academic stress has a positive and significant impact on fatigue, suggesting that high levels of academic stress deplete energy levels and lead to fatigue, which is consistent with the findings of past research. In specific, basing off Yogisutanti's et al (2020) study, the method of "relief" can be explored as cyberloafing, in which sense fatigue would also play a role within the equation. In addition, Hibrain's et al ( 2022) study could also be analyzed in correlation within the study as fatigue was considered an essential variable discovered within the results, and although placing a partial role, was still confirmed within the participants, as such curating similar results.…”
Section: Discussionmentioning
confidence: 99%